Lead-free electronics : (Wiley-Interscience, 2007)
Based on the results of a more than two-year study, Lead-Free Electronics: iNEMI Projects Lead to Successful Manufacturing is the first practical, primary reference to cover Pb-free solder assembly as well as the analysis and reasoning behind the selection of Sn-Ag-Cu as the recommended Pb-free replacement for Sn-Pb.